Spatial Appraisal of the Impacts of Drought on Agricultural Patterns in Karachi - Lubna Ghazal; Syed Jamil H. Kazmi; Sheeba Afsar (Journal of Basic & Applied Sciences, 2021)
This paper is aimed at studying the spatial changes in agricultural patterns practiced in the suburbs of Karachi, which is the most densely populated city of Pakistan with high food demands of the inhabitants. This study deals mainly with Physical factors primarily climatic indicators to observe and analyze the changes in the pattern of agricultural production and the types of crops in last 20-30 years. Variability of climate when coupled with anthropogenic factors play important role in the acceleration of problems for farmers. Trends of associated agricultural output observed in different years of high and low rainfall. This study has successfully demonstrated inquisitive approach by using published secondary data from governmental sources and ground verification in recent times. Temporal variation in biomass, was found dependent upon pattern of rainfall and temperature etc. Study reveals that there are clear signs of desertification and drought in the study area.